PENGARUH POLA ASUH DAN PERAN SAUDARA ASUH TERHADAP KOMPETENSI TERBANG TARUNA AKADEMI PENERBANG INDONESIA BANYUWANGI - radika vatarutama (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
This study aims to determine the effect of the mentorship approach system (character building) analyzed from the stand point of parenting patterns; authoritarian patterns, permissive patterns, democratic patterns on pilot competencies with the intervening role of senior mentor of Indonesia Civil Pilot Academy. The method of this research is quantitative research. The primary data collected in this research is questionnaires. The population of this study are all API Banyuwangi's pilot students which are 67 people with a hierarchical level system of cadets. The technique applied in this research is quantitative statistical analysis through SEM-PLS. The results showed that (Structural Equation Modeling - Partial Least Square) produced the influence of the role of senior mentor with an Adjusted R Square value of 0.291 (29.1%), which means that the Role of senior mentors are influenced by Parenting Patterns by 29.1%. Meanwhile, the Adjusted R Square value of the Competence variable is 0.406 (40.6%), which can be explained that all independent and intervening variables in the SEM model influence Competence by 40.6%.